Inferência do esforço cognitivo despendido em atividades humanas a partir de um sistema sensível ao contexto - Azevedo, Bruno Romero de (2015)
There are different reasons that may collaborate for a human activity to result in damages in one s physical health. Generally, they characterize risk situations that can be avoided, if identified. One of these risks is related to the skill level that a person has to process information, react to his surroundings and make decisions in order to perform an activity, which is determined by the allocation of the mental resources demanded by the activity for its execution. When this allocation is inappropriate, there is a higher possibility for some kind of accident related to the activity to happen due to cognitive overload. This way, it is proposed the development of a model for the inference of such cognitive workload based on models from psychology, especially the skill-rule-knowledge model, concepts from ubiquitous computing and different techniques for the measurement of the cognitive workload. This dissertation is a part of the project Activity Project, which aims to develop a context-aware middleware for the inference and prediction of risks in activities.